What drives subjective well-being in Singapore’s youth? - HO, Kong Weng (Institutional Knowledge at Singapore Management University, 2022)
Subjective well-being, which is the scientific term for happiness and life satisfaction, can impact productivity and health. It is driven by three determining factors – the quality of relationships (relationship stocks), life aspirations and perceived opportunities. Research conducted by SMU Associate Professor Ho Kong Weng examined how these factors affect the subjective well-being of Singapore’s youth.